Electrochemically tuned synergistic nano-interface of a tertiary Ni(OH)(2)-NiO(OH)/NixP heterojunction material for enhanced and durable alkaline water splitting - Manappadan, Zinoy; Selvaraj, Kaliaperumal (ChemistrySelect, 2022)
Making water splitting cheaper is the need of the hour.The present work reports a nickel-based, non-precious catalytic system, synthesized by a two-step electrodeposition (ED) process followed by a short-term heat treatment. The Ni(OH)(2)-NiO(OH)/NixP heterojunction has been synthesized and optimized through an unprecedented, energy-conserving method to achieve its best OER performance. Further, it has been carefully tuned for the first time by thoroughly optimizing the ED parameters to exhibit Hydrogen Evolution Reaction (HER). At high current regimes, the performance surpassed that of the Ru/C and Pt/C (>= 500 mA and >= 600 mA) respectively. The full cell electrolyzer configuring NOPO||NOPH further establishes the supremacy of the present electrocatalysts over the benchmark Ru/C||Pt/C. Moreover, the present electrocatalyst displayed 60 and 70 hours of HER and OER performances at -100 mA and 100 mA currents respectively. In short, this work is an example that illustrates how a single chemical system gets to exhibit two complementary catalytic behaviors that is, water oxidation and reduction when certain synthetic parameters are meticulously optimized.
Keywords: Electrodeposition; heterojunction; Ni(OH)(2)-NiO(OH); NixP; non-precious metal; water splitting

Facile one-pot synthesis of Cu x O/TiO2 photocatalysts by regulating Cu oxidation state for efficient solar H2 production - Rajendran, Sivaraj; Mani, Sunesh S.; Nivedhitha, Thazhath R.; Asoka, Anantha Krishnan; Arun, Pushkaran S.; Mathew, Thomas; Gopinath, Chinnakonda S. (ACS Applied Energy Materials, 2023)
Development of highly efficient CuxO/TiO2 photocatalysts by regulating the oxidation state of Cu exclusively in either single or mixed oxidation state(s) is desirable but difficult to achieve without employing any external reagents. The present work describes a one-pot synthesis strategy to obtain CuxO/TiO2 photocatalysts with Cu in +1 and/or +2 by using a suitable combination of ethylene diamine tetra acetic acid (EDTA) and ethylene diamine, carefully varying the Cu content, and heat treatment process. CuxO/TiO2 nanocomposite catalysts were characterized thoroughly by physicochemical methods. Textural analysis indicates a high dispersion of CuxO on porous TiO2 with p-n heterojunctions between them in CuxO/TiO2 catalysts. UV-visible spectral analysis suggests the presence of CuxO on TiO2 with significantly extended absorption from the UV to the visible region. X-ray photoelectron spectroscopy (XPS) analysis indicates a strong synergetic interaction between TiO2 and CuxO due to the comparable CB potential and p-n heterojunction at the interface among them. Photoelectrochemical studies demonstrate excellent charge-carrier separation efficiency, low charge-transfer resistance, and high double-layer capacitance with Cu2O/TiO2 photocatalysts. Photocatalytic efficacy of a CuxO/TiO2 nanocomposite in thin-film form has been demonstrated for solar hydrogen generation in sunlight. The incorporation of Cu+ in TiO2 largely improves the H-2 production, and all of the CuxO/TiO2 nanocomposites in thin-film form exhibited higher efficiency compared to their particulate/suspension counterpart. Among the composite catalysts, TiCu-1 in thin-film form, with Cu exclusively in +1 oxidation state, exhibited a high hydrogen production rate of 7.06 mmol/hg, which is 6 times higher than its suspension counterpart; also catalysts containing mixed Cu-oxidation states exhibited about 60-70% activity as that of TiCu-1. The superior performance of Cu2O/TiO2 nanocomposites in thin-film form was due to their enhanced light harvesting ability, high mass transfer rate, and easy accessibility of the reactant species to the active sites.
Keywords: heterojunction; Photocatalysis; Solar hydrogen; thin film; titania

Multiphasic heterojunctions: a strategic approach to enhance the charge transfer dynamics of titania for superior solar photocatalytic hydrogen production - Ningthoukhongjam, Pujita; Gopinath, Chinnakonda S.; Nair, Ranjith G. (International Journal of Hydrogen Energy, 2025)
Multiphasic titania has been prepared to study the role of multiple heterojunctions on the charge transfer dynamics and resultant photocatalytic hydrogen production. Through an acid regulated hydrothermal method, four materials with following phase compositions were prepared viz. single phase anatase and rutile, biphasic anatase-rutile and triphasic anatase-brookite-rutile. The phase compositions of the materials were confirmed through XRD and HRTEM studies. The biphasic and triphasic materials were found to be highly nanoparticulate in nature while forming numerous and diverse heterojunctions. In the triphasic material, various binary and ternary heterojunctions were observed. These heterojunctions performed in harmony to ensure efficient charge transport as shown by the low charge transfer resistance and high electron lifetime. This subsequently ensured a high reduction capability and photocurrent response. This all culminated into the triphasic material outperforming all other materials in solar photocatalytic hydrogen production. The H2 yield from the triphasic material was 81% and 40% higher than the pristine anatase and the biphasic material respectively. Additionally, by using the triphasic material in thin film form, a 4-fold increase in the hydrogen yield with a high apparent quantum efficiency of 8.2 % was achieved over the particulate form. The superior charge transport and photocurrent response due to the greater varied heterojunction formation in the anatase-rutile-brookite material as opposed to that in the biphasic material led to this superior performance. Thus, multiple heterojunctions, in this case, a triphasic heterojunction of anatase, rutile and brookite phases opens up a new avenue of research for efficient green hydrogen production.
Keywords: Green hydrogen production; heterojunction; Photocatalysis; Photoelectrochemical analysis; thin film; titania

WS2 nanoparticle-decorated, vertically aligned SnS2-based high-performance heterostructures for ambient-stable ultrafast photodetection - Das, Chayan; Kumar, Suresh; Sharma, Anjali; Kumar, Mahesh; Rath, Arup K.; Sahu, Satyajit (ACS Applied Nano Materials, 2025)
The development of visible-light photodetectors with high responsivity, rapid response, and long-term ambient stability remains a critical challenge in optoelectronics. Here, we report a high-performance photodetector based on a vertically aligned SnS2 film interfaced with WS2 nanoparticles, forming a p-n heterojunction. This device is fabricated using a scalable two-step method-chemical vapor deposition (CVD) for SnS2 growth and solution-based drop-casting for WS2 deposition-enabling precise control over the heterointerface, but trap states are inevitable due to the use of thermal CVD and the drop-casting method. The resulting photodetector exhibits remarkable optoelectronic characteristics, including a responsivity of 0.76 A/W, a detectivity of 7.56 x 10(11) Jones, a photo-to-dark current ratio of 119, and a fast rise time of 0.297 ms under visible illumination. These performance metrics are directly attributed to the optimized heterointerface, where the built-in electric field at the nanoscale WS2/SnS2 junctions promotes efficient charge separation and minimizes recombination losses. Notably, the device retains over 95% of its initial performance even after 1 week of ambient exposure, highlighting its superior environmental robustness. This work introduces an interface-engineering strategy that leverages the unique electronic properties of earth-abundant, nontoxic two-dimensional materials, offering a viable pathway for scalable, high-speed, and stable photodetectors suitable for next-generation optoelectronic systems.
Keywords: 2D; CVD; heterojunction; photodetector; SnS2; WS2